On exact solutions of the nonlinear heat equation - Barannyk, Anatoliy; Yuryk, Ivan (My University, 2019)
A method for construction of exact solutions to nonlinear heat equation ut = (F(u)ux)x + G(u)ux + H(u) which is based on ansatz p(x) = ω1(t) φ(u) + ω2(t) is proposed. The function p(x) here is a solution of equation (p')2 = Ap2 + B, and the functions ω1(t), ω2(t) and φ(u) can be found from the condition that this ansatz reduces the nonlinear heat equation to a system of two ordinary differential equations with unknown functions ω1(t) and ω2(t). Запропоновано метод побудови точних розв’язків нелінійного рівняння теплопровідності ut = (F(u)ux)x + G(u)ux + H(u), який ґрунтується на використанні підстановки p(x) = ω1(t) φ(u) + ω2(t), де функція p(x) є розв’язком рівняння (p')2 = Ap2 + B, а функції ω1(t), ω2(t) та φ(u) знаходяться з умови, що дана підстановка редукує рівняння до системи двох звичайних диференціальних рівнянь з невідомими.
Keywords: кафедра вищої математики імені проф. Можара В. І.; nonlinear hyperbolic equations; generalized separation of variables; вища матиматика; нелінійні гіперболічні рівняння узагальнене відокремлення змінних